REFEREEING PERFORMANCE AND ITS RELATIONSHIP WITH THE PHYSICAL AND MENTAL ABILITIES OF FUTSAL REFEREES - Kamal, Karrar Mustafa; Jabouri, Ayman Hani Abdel (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
Through the researcher's experience as one of the accredited referees in the Iraqi Central Union, and because thesuccess of any referee's performance is largel`y dependent on possessing a wide range of variables mentioned earlier,the researcher was motivated to provide these tests. On the other hand, the researcher aimed to identify these variablesand understand the relationship between them to derive an equation for predicting refereeing performance based on thephysical and mental abilities of futsal referees. This is aimed at improving the reality of this important category toenhance their level as much as possible during their leadership in matches. The research objectives were to know therefereeing performance and the physical and mental abilities of futsal referees and to understand the relationshipbetween refereeing performance and the physical and mental abilities of futsal referees. The researcher used thedescriptive method with a survey approach to measure refereeing performance and the physical and mental abilities offutsal referees. Correlational methods were used to determine the relationship between them and predictive studies topredict refereeing performance based on the physical and mental abilities of futsal referees. The study focused on firstdegree futsal referees in Iraq, totaling (60) referees for the 2022-2024 sports season. The conclusions included theability of the refereeing performance evaluation form prepared to measure and evaluate the refereeing performance offutsal referees. Futsal referees have refereeing performance and physical and mental abilities specific to futsal referees.